Partisipasi Masyarakat dalam Pengelolaan dan Pemanfaatan Dana Desa di Desa Keji Kabupaten Semarang - Asma Luthfi; Hartati Sulistyo Rini; Fulia Aji Gustaman; Thriwaty Arsal; Totok Rochana (Research and Development Agency Ministry of Home Affairs, 2017)
This article aims to explain the participation of the community in the management and utilization of the Dana Desa (DD). This research is located in Keji Village, West Ungaran Sub-district, Semarang Regency with research subject is Keji Village and main informant is community figure, BPD and village apparatus. The type of research used is qualitative research that based its research on the description of field data. Data were obtained through observation, interview, FGD, and documentation study. The results of the study indicate that community knowledge of village funds is limited. Information about the DD management they get from village officials and other citizens through gethok tular. DD in Keji Village amounting to Rp. 608,057,000 is oriented towards infrastructure development, such as paving road, talud, and simple bridge. In the utilization of these DD, communities are involved in the whole process from planning, implementation, to monitoring and evaluation of activities. The study also highlights that community participation in Desa Keji in DD management is still limited to formal participatory activities, centered from the village staff, and administrative order.